1997
DOI: 10.1136/jnnp.63.5.682
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cranial nerve palsies in multiple sclerosis

Abstract: During a 10 year period 24 patients with definite multiple sclerosis with isolated cranial nerve palsies were studied (third and fourth nerve: one patient each, sixth nerve: 12 patients, seventh nerve: three patients, eighth nerve: seven patients), in whom cranial nerve palsies were the presenting sign in 14 and the only clinical sign of an exacerbation in 10 patients. MRI was carried out in 20 patients and substantiated corresponding brainstem lesions in seven patients (third nerve: one patient, sixth nerve: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 20 publications
0
64
1
2
Order By: Relevance
“…In the only study retrospectively investigating isolated cranial nerve palsy in MS, it was found in 1.6% of MS patients 3 . The authors conclude that isolated cranial nerve palsies more often occur as a presenting symptom than during disease relapse (p<0.001), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the only study retrospectively investigating isolated cranial nerve palsy in MS, it was found in 1.6% of MS patients 3 . The authors conclude that isolated cranial nerve palsies more often occur as a presenting symptom than during disease relapse (p<0.001), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
“…Although brainstem involvement is common at MS onset and during the course of the disease, isolated cranial nerve involvement is rare in MS patients. However, magnetic resonance imaging (MRI) may fail to visualize every symptomatic demyelinating lesion [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 İzole kraniyal sinir felçleri ise MS'nin oldukça nadir görülen bulgularındandır. 6 Kraniyal sinir tutulumunun patogenezi tam olarak aydınlatılmamış olsa da birçok çalışmada beyin sapı demyelinizasyonu ile ilişkili olarak saptanmıştır. 7 Beyin sapı tutulumu gerek başlangıçta gerekse ilerleyen hastalık döneminde MS hastalarında sık görülen bir tablodur.…”
Section: Discussionunclassified
“…Regarding various causes of unilateral SOMP, orbital myositis (13,14), thyroid ophthalmopathy (15), trauma (16), surgery (16), cysticercosis (16), peripheral ischemia (16), midbrain stroke (16), congenital (16), multiple sclerosis (17), ophthalmic migraine (18), aneurysm (7,8), cyst (19), neuroborreliosis (20), tumor (9,21), dural carotidcavernous sinus fistula (10), and herpes zoster ophthalmicus (22) have been noted. However, in the present patient, these various causes of unilateral SOMP (7-10, 13-22) could be excluded, based on her clinical course and MR examinations findings.…”
Section: Discussionmentioning
confidence: 99%